Composite rim and preparation method thereof
By designing fixed retaining rings, adjustable retaining rings and laser-sprayed outer sealing coatings on the rims of mining vehicles, the problems of insufficient strength of the existing rim structure and poor adaptability of the vacuum tire are solved, and higher sealing and stability are achieved.
Patent Information
- Application Number
- CN202411902189.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
In the case of large load capacity of existing mining vehicles, the structural strength is insufficient and the adaptability to vacuum tires is poor, which is prone to deformation and damage during use.
A composite rim is designed, including a fixed retaining ring and an adjustable retaining ring, and an external sealing coating obtained by laser spraying is provided to ensure the sealing between the tire and the rim.
By setting up a fixed retaining ring and an adjustable retaining ring, it is convenient for the installation of the internal tires, and the outer sealing coating is sealed and abuts the tires, ensuring the sealing of the pneumatic tires and improving the structural stability and adaptability of the rim.
Smart Images

Figure CN119704937A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a composite wheel rim and a preparation method thereof. Background Art
[0002] The rim is a component used to install and support the tire, and is crucial to maintaining the stability of the tire. Due to the large load capacity of mining vehicles, rims with steel plate roll-welded structures are generally used. Forged rims are lighter, stronger, and have a complex forging process and higher forging costs. In addition to structural strength, casting is less costly than forging, and has poorer adaptability to tires. Generally, tires in the form of inner tubes are less adaptable to vacuum tires and are prone to deformation and damage during use. Summary of the invention
[0003] In order to solve the above problems, the present application proposes a composite rim, including a rim body, a fixed retaining ring is arranged on the outside of one side of the rim body, an adjustable retaining ring is arranged on the other side of the rim body relative to the fixed retaining ring, and an outer sealing coating is arranged on the outward side of the fixed retaining ring and the adjustable retaining ring; the outer sealing coating is obtained by laser spraying. The present application can facilitate the installation of the internal tire by arranging the fixed retaining ring and the adjustable retaining ring, and the outer sealing coating is arranged on the outside, and the outer sealing coating itself can be sealed against the tire, so that the inflated tire and the outer sealing coating have sufficient sealing performance to ensure the sealing effect.
[0004] Preferably, the outer sealing coating comprises a base layer arranged on the inner side and an abutting layer arranged on the base layer, the base layer has a thickness of 50-100 μm, and the abutting layer has a thickness of 200-300 μm;
[0005] The base layer includes the following raw materials in parts by weight:
[0006] Al: 6-8 parts; Sn: 1.5-2.5 parts;
[0007] The abutting layer includes the following raw materials in parts by weight:
[0008] Al: 20-30 parts; Cr: 2-4 parts; Cu: 1-2 parts; Nano-white carbon black: 1-2 parts; WC: 0.2-0.4 parts. The present application adopts Al and Sn to form the base layer, and Al, Cr, Cu, nano-white carbon black and WC to form the abutment layer, which ensures the bonding strength between the abutment layer and the rim body, and the nano-white carbon black and WC are arranged on the outside to make the tire more stably attached to the abutment layer.
[0009] Preferably, the outer sealing coating is operated according to the following steps:
[0010] Place the fixed retaining ring and the adjustable retaining ring facing outward into acetone for ultrasonic cleaning for 0.5-1h, and then blow dry;
[0011] Laser-assisted spraying for spraying of base layer and abutting layer:
[0012] For the base layer, keep the laser spot and the spray powder spot aligned in the center. 2 The pressure is 0.8-1MPa, the preheating temperature is 520-550℃, the spraying distance is 18-20mm, the scanning speed is 40-50mm / s, the powder feeding rate is 10-15g / min, and the laser irradiation power is 500-600W;
[0013] For the abutting layer, after the base layer is coated, the abutting layer is coated immediately, and the laser spot and the spray powder spot are kept in the same center. 2 The pressure is 0.8-1MPa, the preheating temperature is 520-550℃, the spraying distance is 18-20mm, the scanning speed is 20-25mm / s, the powder feeding rate is 20-25g / min, and the laser irradiation power is 600-800W;
[0014] The diameter of the laser spot is 5-6 mm; the diameter of the spray powder spot is 4-5 mm.
[0015] Preferably, a clamping groove is provided on the rim body at the lower part of the adjustable retaining ring, a locking ring is clamped in the clamping groove, and the locking ring is abutted against a side of the adjustable retaining ring away from the fixed retaining ring;
[0016] The locking ring comprises a clamping block inserted into the clamping groove, an obliquely arranged oblique block is arranged on the clamping block, an oblique positioning surface is arranged at a position of the oblique block relative to the adjustable retaining ring; an oblique abutting surface abutting against the oblique positioning surface is arranged at a position of the adjustable retaining ring corresponding to the oblique block;
[0017] The adjustable retaining ring includes an abutting plate abutting against the rim body, a vertical retaining plate is arranged on the side of the abutting plate away from the fixed retaining ring, a transverse plate is arranged on the side of the vertical retaining plate away from the fixed retaining ring, and a connecting part of the abutting plate and the vertical retaining plate is obliquely arranged on the side adjacent to the rim body to form an oblique positioning surface. The present application can play a guiding and positioning role when abutting by setting the oblique abutting surface and the oblique positioning surface, so that the clamping block can stably slide into the clamping groove, and then complete the structural clamping, ensuring the assemblability of the structure.
[0018] Preferably, an auxiliary groove is further provided on a side of the clamping groove close to the rim body;
[0019] A transition groove is arranged at the position of the auxiliary groove corresponding to the abutment plate, and one end of the transition groove facing the fixed retaining ring is arranged at the upper part of the auxiliary groove; one end of the transition groove away from the fixed retaining ring is smoothly connected to the oblique positioning surface.
[0020] Preferably, an annular groove is provided on the side of the abutment plate facing the rim body, and an annular sealing ring is provided in the annular groove; a valve channel is provided on the hub body, and a concave valve sealing ring is provided on the outward side of the valve channel.
[0021] Preferably, the side of the clamping groove facing away from the fixed retaining ring is a first clamping angle, and the side close to the fixed retaining ring is a second clamping angle; the second clamping angle is larger than the first clamping angle; the first clamping angle is a right angle; a positioning clamping groove matched with the first clamping angle is formed between the clamping block and the oblique block. The present application can ensure that the positioning clamping groove is clamped into the first clamping angle through the matching setting of the first clamping angle and the second clamping angle, and the structural deformation will not occur, and the stability after assembly is also good. When it needs to be taken out, it can be easily slid out because the second clamping angle is an obtuse angle. Through the design of the transition groove, a lever structure with this place as the fulcrum and the distal abutment plate as the contact point is formed, and its own structural stability and sealing strength are more effectively guaranteed.
[0022] Preferably, an outer protective plate is provided on the rim body on one side of the adjustable retaining ring, a plurality of bolt connection holes are provided on the outer protective plate, an oblique connecting plate is provided between the outer protective plate and the rim body, a plurality of ventilation holes are provided on the oblique connecting plate; the adjustable retaining ring is provided in an integrated manner.
[0023] On the other hand, the present application also discloses a method for preparing a composite rim, which is characterized by comprising the following steps:
[0024] S1. Develop an iron-mold-coated sand composite rim mold according to the size of the composite rim;
[0025] S2. Conduct full-size inspection on the iron-mold-covered sand composite rim mold, and transfer it to the foundry workshop for production after it passes the inspection;
[0026] S3. Before production, the iron mold coated with sand composite rim mold is heated to 230 ° C by electric heating pipe, and the coated sand is shot into the composite rim cavity by a sand shooting machine. After 3 minutes, the mold is opened, the vent core is lowered, and the surrounding sealing paste is applied to close the upper and lower boxes and tighten them, and then the casting material is poured into the casting section;
[0027] S4. Cool down for 40 minutes after pouring and unpack;
[0028] S5. Transfer to the shot blasting and grinding station, after air cooling, carry out shot blasting and sand removal at a temperature below 50℃, remove the pouring head, grind the flash and burrs, and transfer to the heat treatment station after passing the inspection;
[0029] S6. The heat treatment furnace is heated to 880℃-900℃, kept in the furnace for 150 minutes, cooled naturally to 700℃, and then transferred to the processing procedure after passing the air cooling inspection;
[0030] S7. Process to finished product size, and transfer to painting process after passing inspection.
[0031] Preferably, the raw materials of the iron mold-covered sand composite rim mold include the following raw materials in parts by mass:
[0032] Silica sand: 100-120 parts;
[0033] Bentonite: 3-5 parts;
[0034] Water glass: 1-2 parts;
[0035] Titanium dioxide: 0.5-1 part;
[0036] The pouring is carried out as follows:
[0037] The casting material is added into a medium frequency electric furnace, heated to 1500-1520°C and then subjected to a spheroidizing treatment. The casting material includes the following raw materials:
[0038] 3.7wt%≤C≤3.9wt%;
[0039] 2.1wt%≤Si≤2.6wt%;
[0040] 0.3wt%≤Mn≤0.5wt%;
[0041] 0.01wt%≤S≤0.03wt%;
[0042] 0.02wt%≤P≤0.05wt%;
[0043] 0.03wt%≤Mg≤0.06wt%;
[0044] 0.05wt%≤Cu≤0.07wt%;
[0045] The rest is Fe;
[0046] The coating process is carried out as follows:
[0047] Place the fixed retaining ring and the adjustable retaining ring facing outward into acetone for ultrasonic cleaning for 0.5-1h, and then blow dry;
[0048] Laser-assisted spraying for spraying of base layer and abutting layer:
[0049] For the base layer, keep the laser spot and the spray powder spot aligned in the center. 2The pressure is 0.8-1MPa, the preheating temperature is 520-550℃, the spraying distance is 18-20mm, the scanning speed is 40-50mm / s, the powder feeding rate is 10-15g / min, and the laser irradiation power is 500-600W;
[0050] For the abutting layer, after the base layer is coated, the abutting layer is coated immediately, and the laser spot and the spray powder spot are kept in the same center. 2 The pressure is 0.8-1MPa, the preheating temperature is 520-550℃, the spraying distance is 18-20mm, the scanning speed is 20-25mm / s, the powder feeding rate is 20-25g / min, and the laser irradiation power is 600-800W;
[0051] The diameter of the laser spot is 5-6 mm; the diameter of the spray powder spot is 4-5 mm;
[0052] The base layer includes the following raw materials in parts by weight:
[0053] Al: 6-8 parts; Sn: 1.5-2.5 parts;
[0054] The abutting layer includes the following raw materials in parts by weight:
[0055] Al: 20-30 parts; Cr: 2-4 parts; Cu: 1-2 parts; Nano-silica: 1-2 parts; WC: 0.2-0.4 parts.
[0056] This application can bring the following beneficial effects:
[0057] 1. The present application can facilitate the installation of the internal tire by providing a fixed retaining ring and an adjustable retaining ring, and an external sealing coating is provided on the outside. The external sealing coating itself can be sealed against the tire, so that the inflated tire and the external sealing coating have sufficient sealing properties to ensure the sealing effect.
[0058] 2. The present application adopts Al and Sn to form the base layer, and Al, Cr, Cu, nano-silica and WC to form the abutment layer, which ensures the bonding strength between the abutment layer and the rim body, and the nano-silica and WC are arranged on the outside to make the tire more stably attached to the abutment layer.
[0059] 3. The present application can ensure that the positioning clamping groove is clamped into the first clamping angle through the coordinated setting of the first clamping angle and the second clamping angle, and no structural deformation will occur. The stability after assembly is also good. When it needs to be taken out, since the second clamping angle is an obtuse angle, it can also be easily slid out. Through the design of the transition groove, a lever structure is formed with this place as the fulcrum and the distal abutment plate as the contact point, and its own structural stability and sealing strength are more effectively guaranteed. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0061] Figure 1 This is a schematic diagram of the structure of this application.
[0062] Figure 2 Schematic diagram of the structure of the adjustable retaining ring part assembly. DETAILED DESCRIPTION
[0063] In order to clearly illustrate the technical features of the present solution, the present application is described in detail below through specific implementation methods and in conjunction with the accompanying drawings.
[0064] For the structural part, such as Figure 1-2 As shown, a rim structure for a vacuum tire comprises a rim body 1, a fixed retaining ring 2 is arranged on the outside of one side of the rim body 1, an adjustable retaining ring 3 is arranged on the other side of the rim body 1 relative to the fixed retaining ring 2, an outer sealing coating 31 is arranged on the outward side of the fixed retaining ring 2 and the adjustable retaining ring 3; the outer sealing coating 31 is obtained by laser spraying; the outer sealing coating 31 comprises a base layer 32 arranged on the inner side and a contact layer 33 arranged on the base layer 32, the base layer 32 has a thickness of 50-100 μm, and the contact layer 33 has a thickness of 200-300 μm.
[0065] A clamping groove 4 is provided on the rim body 1 below the adjustable retaining ring 3 , and a locking ring 5 is clamped in the clamping groove 4 . The locking ring 5 is abutted against a side of the adjustable retaining ring 3 away from the fixed retaining ring 2 .
[0066] The locking ring 5 includes a clamping block 6 inserted into the clamping groove 4, an obliquely arranged oblique block 7 is arranged on the clamping block 6, an oblique positioning surface 8 is arranged at the position of the oblique block 7 relative to the adjustable retaining ring 3; an oblique abutting surface 9 is arranged at the position of the adjustable retaining ring 3 corresponding to the oblique block 7 and abutted with the oblique positioning surface 8. The adjustable retaining ring 3 includes an abutting plate 10 abutting against the rim body 1, a vertical baffle 11 is arranged on the side of the abutting plate 10 away from the fixed retaining ring 2, a transverse plate 12 is arranged on the side of the vertical baffle 11 away from the fixed retaining ring 2, and the connection between the abutting plate 10 and the vertical baffle 11 is obliquely arranged on the side adjacent to the rim body 1 to form an oblique positioning surface 8. An auxiliary groove 13 is also arranged on the side of the clamping groove 4 close to the rim body 1. A transition groove 14 is provided at the position of the auxiliary groove 13 corresponding to the abutment plate 10, and one end of the transition groove 14 facing the fixed retaining ring 2 is provided at the upper part of the auxiliary groove 13; one end of the transition groove 14 away from the fixed retaining ring 2 is smoothly connected to the oblique positioning surface 8. An annular groove 15 is provided on the side of the abutment plate 10 facing the rim body 1, and an annular sealing ring 16 is provided in the annular groove 15.
[0067] The side of the clamping groove 4 facing away from the fixed retaining ring 2 is a first clamping angle 17 (α), and the side close to the fixed retaining ring 2 is a second clamping angle 18 (β); the second clamping angle 18 (β) is greater than the first clamping angle 17 (α); the first clamping angle 17 (α) is a right angle; a positioning clamping groove 19 is formed between the clamping block 6 and the oblique block 7 to cooperate with the first clamping angle 17 (α).
[0068] An outer protective plate 20 is arranged on the rim body 1 on one side of the adjustable retaining ring 3 , a plurality of bolt connection holes 21 are arranged on the outer protective plate 20 , an oblique connecting plate 22 is arranged between the outer protective plate 20 and the rim body 1 , a plurality of ventilation holes 23 are arranged on the oblique connecting plate 22 .
[0069] The adjustable retaining ring 3 is integrally arranged. A valve channel 24 is arranged on the wheel hub body 1, and a valve concave sealing ring 25 is arranged on the outward side of the valve channel 24.
[0070] When in use, after the vacuum tire is installed on the rim body 1, press the two sides with a crowbar, put the annular sealing ring 16 in the annular groove of the rim body 1, and then install the adjustable retaining ring 3 to squeeze it on the top, and then install the locking ring 5 in the clamping groove 4, so that the oblique abutting surface 9 and the oblique positioning surface 8 can play a guiding and positioning role when abutting, so that the clamping block 6 can stably slide into the clamping groove, and then complete the structural clamping, and through the coordinated setting of the first clamping angle 17 and the second clamping angle 18, it can be ensured that the positioning clamping groove 19 is clamped into the first clamping angle 17, and no structural deformation will occur. The stability after assembly is also good, and when it needs to be taken out, since the second clamping angle 18 is an obtuse angle, it can also be easily slid out; finally, after the vacuum tire is inflated, it can play a sealing role.
[0071] In the second embodiment, the same rim is prepared according to the structure shown in the embodiment 1, and different outer sealing coatings 31 are prepared on the rim. The preparation is specifically carried out in the following manner:
[0072] In terms of the preparation method, the present application also discloses a method for preparing a composite rim, comprising the following steps:
[0073] S1. Develop an iron-mold-coated sand composite rim mold according to the size of the composite rim;
[0074] The raw materials of the iron mold covered with sand composite rim mold include the following raw materials in parts by mass:
[0075] Silica sand: 100-120 parts;
[0076] Bentonite: 3-5 parts;
[0077] Water glass: 1-2 parts;
[0078] Titanium dioxide: 0.5-1 part;
[0079] S2. Conduct full-size inspection on the iron-mold-covered sand composite rim mold, and transfer it to the foundry workshop for production after it passes the inspection;
[0080] S3. Before production, the iron mold coated with sand composite rim mold is heated to 230 ° C by electric heating pipe, and the coated sand is shot into the composite rim cavity by a sand shooting machine. After 3 minutes, the mold is opened, the vent core is lowered, and the surrounding sealing paste is applied to close the upper and lower boxes and tighten them, and then the casting material is poured into the casting section;
[0081] The casting material is added into a medium frequency electric furnace, heated to 1500-1520°C and then subjected to a spheroidizing treatment. The casting material includes the following raw materials:
[0082] 3.7wt%≤C≤3.9wt%;
[0083] 2.1wt%≤Si≤2.6wt%;
[0084] 0.3wt%≤Mn≤0.5wt%;
[0085] 0.01wt%≤S≤0.03wt%;
[0086] 0.02wt%≤P≤0.05wt%;
[0087] 0.03wt%≤Mg≤0.06wt%;
[0088] 0.05wt%≤Cu≤0.07wt%;
[0089] The rest is Fe;
[0090] S4. Cool down for 40 minutes after pouring and unpack;
[0091] S5. Transfer to the shot blasting and grinding station, after air cooling, carry out shot blasting and sand removal at a temperature below 50℃, remove the pouring head, grind the flash and burrs, and transfer to the heat treatment station after passing the inspection;
[0092] S6. The heat treatment furnace is heated to 880℃-900℃, kept in the furnace for 150 minutes, cooled naturally to 700℃, and then transferred to the processing procedure after passing the air cooling inspection;
[0093] S7. Process to finished product size, and transfer to painting process after passing inspection.
[0094] The coating process is carried out as follows:
[0095] Place the fixed retaining ring and the adjustable retaining ring facing outward into acetone for ultrasonic cleaning for 0.5-1h, and then blow dry;
[0096] Laser-assisted spraying for spraying of base layer and abutting layer:
[0097] For the base layer, keep the laser spot and the spray powder spot aligned in the center. 2 The pressure is 0.8-1MPa, the preheating temperature is 520-550℃, the spraying distance is 18-20mm, the scanning speed is 40-50mm / s, the powder feeding rate is 10-15g / min, and the laser irradiation power is 500-600W;
[0098] For the abutting layer, after the base layer is coated, the abutting layer is coated immediately, and the laser spot and the spray powder spot are kept in the same center. 2 The pressure is 0.8-1MPa, the preheating temperature is 520-550℃, the spraying distance is 18-20mm, the scanning speed is 20-25mm / s, the powder feeding rate is 20-25g / min, and the laser irradiation power is 600-800W;
[0099] The diameter of the laser spot is 5-6 mm; the diameter of the spray powder spot is 4-5 mm;
[0100] The base layer includes the following raw materials in parts by weight:
[0101] Al: 6-8 parts; Sn: 1.5-2.5 parts;
[0102] The abutting layer includes the following raw materials in parts by weight:
[0103] Al: 20-30 parts; Cr: 2-4 parts; Cu: 1-2 parts; Nano-silica: 1-2 parts; WC: 0.2-0.4 parts.
[0104] With specific reference to the structural part, experiments were carried out using rims of the same size and structure and with the same vacuum tire installed outside the rim.
[0105] Embodiment 1:
[0106] S101. Develop an iron-coated sand composite rim mold according to the size of the composite rim;
[0107] The raw materials of the iron mold covered with sand composite rim mold include the following raw materials in parts by mass:
[0108] Silica sand: 100 parts;
[0109] Bentonite: 3 parts;
[0110] Water glass: 1 part;
[0111] Titanium dioxide: 0.5 parts;
[0112] S102. Conduct full-size inspection on the iron mold covered with sand composite rim mold, and transfer it to the foundry workshop for production after it passes the inspection;
[0113] S103. Before production, the iron mold coated with sand composite rim mold is heated to 230°C by electric heating pipe, and the coated sand is shot into the composite rim cavity by a sand shooting machine. After 3 minutes, the mold is opened, the vent core is lowered, and the surrounding sealing paste is applied to close the upper and lower boxes and tighten them, and then the casting material is poured into the casting section;
[0114] The casting material is added into a medium frequency electric furnace, heated to 1500°C and then subjected to a spheroidizing treatment. The casting material includes the following raw materials:
[0115] C: 3.7wt%;
[0116] Si: 2.1wt%;
[0117] Mn: 0.3wt%;
[0118] S: 0.01wt%;
[0119] P: 0.02wt%;
[0120] Mg: 0.03wt%;
[0121] Cu: 0.05wt%;
[0122] The rest is Fe;
[0123] S104. Cool down for 40 minutes after pouring and unpack;
[0124] S105. Transfer to the shot blasting and grinding station, after air cooling, perform shot blasting and sand removal at a temperature below 50°C, remove the pouring head, grind the flash and burrs, and transfer to the heat treatment station after passing the inspection;
[0125] S106. The heat treatment furnace is heated to 880°C, kept in the furnace for 150 minutes, cooled naturally to 700°C, and then transferred to the processing procedure after passing the air cooling inspection;
[0126] S107. Process to finished product size, and transfer to painting process after passing inspection.
[0127] The coating process is carried out as follows:
[0128] Place the fixed retaining ring and the adjustable retaining ring facing outward into acetone for ultrasonic cleaning for 0.5 h, and then blow dry;
[0129] Laser-assisted spraying for spraying of base layer and abutting layer:
[0130] For the base layer, keep the laser spot and the spray powder spot aligned in the center. 2 The pressure is 0.8MPa, the preheating temperature is 520℃, the spraying distance is 18mm, the scanning speed is 40mm / s, the powder feeding rate is 10g / min, and the laser irradiation power is 500W;
[0131] For the abutting layer, after the base layer is coated, the abutting layer is coated immediately, and the laser spot and the spray powder spot are kept in the same center. 2 The pressure is 0.8MPa, the preheating temperature is 520℃, the spraying distance is 18mm, the scanning speed is 20mm / s, the powder feeding rate is 20g / min, and the laser irradiation power is 600W;
[0132] The diameter of the laser spot is 5 mm; the diameter of the spray powder spot is 4 mm;
[0133] The base layer includes the following raw materials in parts by weight:
[0134] Al: 6 parts; Sn: 1.55 parts;
[0135] The abutting layer includes the following raw materials in parts by weight:
[0136] Al: 20 parts; Cr: 2 parts; Cu: 1 part; Nano-silica: 1 part; WC: 0.2 parts.
[0137] Place the matching vacuum tire cover on the outside of the obtained rim (a set of 10 is required), take one of them, and place it under 9MPa and room temperature for 24 hours. If there is no leakage, set the initial air pressure to 9MPa, and measure the air pressure after 30 days. The air pressure value is 8.9MPa.
[0138] The obtained tire was assembled on a suitable wheel, and emergency braking was performed 50 times under the conditions of a driving speed of 25 km / h and an air pressure of 9 MPa to measure the offset between the rim and the tire. The evaluation results were expressed by setting Example 1 as 1, and the remaining examples were divided by the offset of Example 1 to represent the final offset.
[0139] Embodiment 2:
[0140] S201. Develop iron mold covered with sand composite rim mold according to the size of the composite rim;
[0141] The raw materials of the iron mold covered with sand composite rim mold include the following raw materials in parts by mass:
[0142] Silica sand: 120 parts;
[0143] Bentonite: 5 parts;
[0144] Water glass: 2 parts;
[0145] Titanium dioxide: 1 part;
[0146] S202. Conduct full-size inspection on the iron mold covered with sand composite rim mold, and transfer it to the foundry workshop for production after passing the inspection;
[0147] S203. Before production, the iron mold coated with sand composite rim mold is heated to 230 ° C by electric heating pipe, and the coated sand is shot into the composite rim cavity by a sand shooting machine. After 3 minutes, the mold is opened, the vent core is lowered, and the surrounding sealing paste is applied to close the upper and lower boxes and tighten them, and then the casting material is poured into the casting section;
[0148] The casting material is added into a medium frequency electric furnace, and the temperature is raised to 1520°C before being subjected to a spheroidizing treatment. The casting material includes the following raw materials:
[0149] C: 3.9wt%;
[0150] Si: 2.6wt%;
[0151] Mn: 0.5wt%;
[0152] S: 0.03wt%;
[0153] P: 0.05wt%;
[0154] Mg: 0.06wt%;
[0155] Cu: 0.07wt%;
[0156] The rest is Fe;
[0157] S204. Cool down for 40 minutes after pouring and unpack;
[0158] S205. Transfer to the shot blasting and grinding station, after air cooling, perform shot blasting and sand removal at a temperature below 50°C, remove the pouring head, grind the flash and burrs, and transfer to the heat treatment station after passing the inspection;
[0159] S206. The heat treatment furnace is heated to 900°C, kept in the furnace for 150 minutes, cooled naturally to 700°C, and then transferred to the processing procedure after passing the air cooling inspection;
[0160] S207. Process to finished product size, and transfer to painting process after passing inspection.
[0161] The coating process is carried out as follows:
[0162] Place the fixed retaining ring and the adjustable retaining ring facing outward into acetone for ultrasonic cleaning for 1 hour, and then blow dry;
[0163] Laser-assisted spraying for spraying of base layer and abutting layer:
[0164] For the base layer, keep the laser spot and the spray powder spot aligned in the center. 2 The pressure is 1MPa, the preheating temperature is 550℃, the spraying distance is 20mm, the scanning speed is 50mm / s, the powder feeding rate is 15g / min, and the laser irradiation power is 600W;
[0165] For the abutting layer, after the base layer is coated, the abutting layer is coated immediately, and the laser spot and the spray powder spot are kept in the same center. 2 The pressure is 1MPa, the preheating temperature is 550℃, the spraying distance is 20mm, the scanning speed is 25mm / s, the powder feeding rate is 25g / min, and the laser irradiation power is 800W;
[0166] The diameter of the laser spot is 6 mm; the diameter of the spray powder spot is 5 mm;
[0167] The base layer includes the following raw materials in parts by weight:
[0168] Al: 8 parts; Sn: 2.5 parts;
[0169] The abutting layer includes the following raw materials in parts by weight:
[0170] Al: 30 parts; Cr: 4 parts; Cu: 2 parts; Nano-silica: 2 parts; WC: 0.4 parts.
[0171] Place the matching vacuum tire cover on the outside of the obtained rim (a set of 10 is required), take one of them, and place it under 9MPa and room temperature for 24 hours. If there is no leakage, set the initial air pressure to 9MPa, and measure the air pressure after 30 days. The air pressure value is 8.9MPa.
[0172] The obtained tire was assembled on a suitable wheel, and emergency braking was performed 50 times under the conditions of a driving speed of 25 km / h and an air pressure of 9 MPa to measure the offset between the rim and the tire. The evaluation results were expressed by setting Example 1 as 1, and the offset of the remaining examples divided by Example 1 as the final offset representation value. The offset of this test was 0.99.
[0173] Comparative Example 1:
[0174] S301. Develop an iron mold covered with sand composite rim mold according to the size of the composite rim;
[0175] The raw materials of the iron mold covered with sand composite rim mold include the following raw materials in parts by mass:
[0176] Silica sand: 100 parts;
[0177] Bentonite: 3 parts;
[0178] Water glass: 1 part;
[0179] Titanium dioxide: 0.5 parts;
[0180] S302. Conduct full-size inspection on the iron mold covered with sand composite rim mold, and transfer it to the foundry workshop for production after passing the inspection;
[0181] S303. Before production, the iron mold coated with sand composite rim mold is heated to 230 ° C by electric heating pipe, and the coated sand is shot into the composite rim cavity by a sand shooting machine. After 3 minutes, the mold is opened, the vent core is lowered, and the surrounding sealing paste is applied to close the upper and lower boxes and tighten them, and then the casting material is poured into the casting section;
[0182] The casting material is added into a medium frequency electric furnace, heated to 1500°C and then subjected to a spheroidizing treatment. The casting material includes the following raw materials:
[0183] C: 3.7wt%;
[0184] Si: 2.1wt%;
[0185] Mn: 0.3wt%;
[0186] S: 0.01wt%;
[0187] P: 0.02wt%;
[0188] Mg: 0.03wt%;
[0189] Cu: 0.05wt%;
[0190] The rest is Fe;
[0191] S304. Cool down for 40 minutes after pouring and unpack;
[0192] S305. Transfer to the shot blasting and grinding station, after air cooling, perform shot blasting and sand removal at a temperature below 50°C, remove the pouring head, grind the flash and burrs, and transfer to the heat treatment station after passing the inspection;
[0193] S306. The heat treatment furnace is heated to 880°C, kept in the furnace for 150 minutes, cooled naturally to 700°C, and then transferred to the processing procedure after passing the air cooling inspection;
[0194] S307. Process to finished product size, and transfer to painting process after passing inspection.
[0195] The coating process is carried out as follows:
[0196] Place the fixed retaining ring and the adjustable retaining ring facing outward into acetone for ultrasonic cleaning for 0.5 h, and then blow dry;
[0197] Spraying of the abutting layer using laser-assisted spraying:
[0198] For the abutting layer, keep the laser spot and the spray powder spot aligned in the center. 2 The pressure is 0.8MPa, the preheating temperature is 520℃, the spraying distance is 18mm, the scanning speed is 20mm / s, the powder feeding rate is 20g / min, and the laser irradiation power is 600W;
[0199] The diameter of the laser spot is 5 mm; the diameter of the spray powder spot is 4 mm;
[0200] The abutting layer includes the following raw materials in parts by weight:
[0201] Al: 20 parts; Cr: 2 parts; Cu: 1 part; Nano-silica: 1 part; WC: 0.2 parts.
[0202] Place the matching vacuum air conditioning tire cover on the outside of the obtained rim (a set of 10 is required), take one of them, and place it under 9MPa and room temperature for 24 hours. If there is no leakage, set the initial air pressure to 9MPa, and measure the air pressure after 30 days. The air pressure value is 8.5MPa;
[0203] The obtained tire was assembled on a suitable wheel, and emergency braking was performed 50 times under the conditions of a driving speed of 25 km / h and an air pressure of 9 MPa to measure the offset between the rim and the tire. The evaluation results were expressed by setting Example 1 as 1, and the offset of the remaining examples divided by Example 1 was used as the representative value of the final offset. The offset of this test was 1.02.
[0204] Comparative Example 2:
[0205] S401. Develop an iron-coated sand composite rim mold according to the size of the composite rim;
[0206] The raw materials of the iron mold covered with sand composite rim mold include the following raw materials in parts by mass:
[0207] Silica sand: 100 parts;
[0208] Bentonite: 3 parts;
[0209] Water glass: 1 part;
[0210] Titanium dioxide: 0.5 parts;
[0211] S402. Conduct full-size inspection on the iron mold covered with sand composite rim mold, and transfer it to the foundry workshop for production after it passes the inspection;
[0212] S403. Before production, the iron mold coated with sand composite rim mold is heated to 230 ° C by electric heating pipe, and the coated sand is shot into the composite rim cavity by a sand shooting machine. After 3 minutes, the mold is opened, the vent core is lowered, and the surrounding sealing paste is applied to close the upper and lower boxes and tighten them, and then the casting material is poured into the casting section;
[0213] The casting material is added into a medium frequency electric furnace, heated to 1500°C and then subjected to a spheroidizing treatment. The casting material includes the following raw materials:
[0214] C: 3.7wt%;
[0215] Si: 2.1wt%;
[0216] Mn: 0.3wt%;
[0217] S: 0.01wt%;
[0218] P: 0.02wt%;
[0219] Mg: 0.03wt%;
[0220] Cu: 0.05wt%;
[0221] The rest is Fe;
[0222] S404. Cool down for 40 minutes after pouring and unpack;
[0223] S405. Transfer to the shot blasting and grinding station, after air cooling, carry out shot blasting and sand removal at a temperature below 50°C, remove the pouring head, grind the flash and burrs, and transfer to the heat treatment station after passing the inspection;
[0224] S406. The heat treatment furnace is heated to 880°C, kept in the furnace for 150 minutes, cooled naturally to 700°C, and then transferred to the processing procedure after passing the air cooling inspection;
[0225] S407. Process to finished product size and pass inspection.
[0226] Place the matching vacuum air conditioning tire cover on the outside of the obtained rim (a set of 10 is required), take one of them, and place it under 9MPa and room temperature for 24 hours. If there is no leakage, set the initial air pressure to 9MPa, and measure the air pressure after 30 days. The air pressure value is 8.3MPa;
[0227] The obtained tire was assembled on a suitable wheel, and emergency braking was performed 50 times under the conditions of a driving speed of 25 km / h and an air pressure of 9 MPa to measure the offset between the rim and the tire. The evaluation results were expressed by setting Example 1 as 1, and the offset of the remaining examples divided by Example 1 was used as the representative value of the final offset. The offset of this test was 1.05.
[0228] Comparative Example 3:
[0229] S501. Develop iron mold covered with sand composite rim mold according to the size of the composite rim;
[0230] The raw materials of the iron mold covered with sand composite rim mold include the following raw materials in parts by mass:
[0231] Silica sand: 100 parts;
[0232] Bentonite: 3 parts;
[0233] Water glass: 1 part;
[0234] Titanium dioxide: 0.5 parts;
[0235] S502. Conduct full-size inspection on the iron mold covered with sand composite rim mold, and transfer it to the foundry workshop for production after passing the inspection;
[0236] S503. Before production, the iron mold coated with sand composite rim mold is heated to 230 ° C by electric heating pipe, and the coated sand is shot into the composite rim cavity by a sand shooting machine. After 3 minutes, the mold is opened, the vent core is lowered, and the surrounding sealing paste is applied to close the upper and lower boxes and tighten them, and then the casting material is poured into the casting section;
[0237] The casting material is added into a medium frequency electric furnace, heated to 1500°C and then subjected to a spheroidizing treatment. The casting material includes the following raw materials:
[0238] C: 3.7wt%;
[0239] Si: 2.1wt%;
[0240] Mn: 0.3wt%;
[0241] S: 0.01wt%;
[0242] P: 0.02wt%;
[0243] Mg: 0.03wt%;
[0244] Cu: 0.05wt%;
[0245] The rest is Fe;
[0246] S504. Cool down for 40 minutes after pouring and unpack;
[0247] S505. Transfer to the shot blasting and grinding station, after air cooling, perform shot blasting and sand removal at a temperature below 50°C, remove the pouring head, grind the flash and burrs, and transfer to the heat treatment station after passing the inspection;
[0248] S506. The heat treatment furnace is heated to 880°C, kept in the furnace for 150 minutes, cooled naturally to 700°C, and then transferred to the processing procedure after passing the air cooling inspection;
[0249] S507. Process to finished product size, and transfer to painting process after passing inspection.
[0250] The coating process is carried out as follows:
[0251] Place the fixed retaining ring and the adjustable retaining ring facing outward into acetone for ultrasonic cleaning for 0.5 h, and then blow dry;
[0252] Laser-assisted spraying for spraying of base layer and abutting layer:
[0253] For the base layer, keep the laser spot and the spray powder spot aligned in the center. 2 The pressure is 0.8MPa, the preheating temperature is 520℃, the spraying distance is 18mm, the scanning speed is 40mm / s, the powder feeding rate is 10g / min, and the laser irradiation power is 500W;
[0254] For the abutting layer, after the base layer is coated, the abutting layer is coated immediately, and the laser spot and the spray powder spot are kept in the same center. 2 The pressure is 0.8MPa, the preheating temperature is 520℃, the spraying distance is 18mm, the scanning speed is 20mm / s, the powder feeding rate is 20g / min, and the laser irradiation power is 600W;
[0255] The diameter of the laser spot is 5 mm; the diameter of the spray powder spot is 4 mm;
[0256] The base layer is an aluminum layer:
[0257] The abutting layer includes the following raw materials in parts by weight:
[0258] Al: 20 parts; Cr: 2 parts; Cu: 1 part; Nano-silica: 1 part; WC: 0.2 parts.
[0259] Place the matching vacuum air conditioning tire cover on the outside of the obtained rim (a set of 10 is required), take one of them, and place it under 9MPa and room temperature for 24 hours. If there is no leakage, set the initial air pressure to 9MPa, and measure the air pressure after 30 days. The air pressure value is 8.4MPa.
[0260] The obtained tire was assembled on a suitable wheel, and emergency braking was performed 50 times under the conditions of a driving speed of 25 km / h and an air pressure of 9 MPa to measure the offset between the rim and the tire. The evaluation results were expressed by setting Example 1 as 1, and the offset of the remaining examples divided by Example 1 was used as the representative value of the final offset. The offset of this test was 1.04.
[0261] Comparative Example 4:
[0262] S601. Develop iron-coated sand composite rim mold according to the size of the composite rim;
[0263] The raw materials of the iron mold covered with sand composite rim mold include the following raw materials in parts by mass:
[0264] Silica sand: 100 parts;
[0265] Bentonite: 3 parts;
[0266] Water glass: 1 part;
[0267] Titanium dioxide: 0.5 parts;
[0268] S602. Conduct full-size inspection on the iron mold covered with sand composite rim mold, and transfer it to the foundry workshop for production after it passes the inspection;
[0269] S603. Before production, the iron mold coated with sand composite rim mold is heated to 230°C by an electric heating tube, and the coated sand is shot into the composite rim cavity by a sand shooting machine. After 3 minutes, the mold is opened, the vent core is lowered, and the surrounding sealing paste is applied to close the upper and lower boxes and tighten them, and then the casting material is poured into the casting section;
[0270] The casting material is added into a medium frequency electric furnace, heated to 1500°C and then subjected to a spheroidizing treatment. The casting material includes the following raw materials:
[0271] C: 3.7wt%;
[0272] Si: 0.2wt%;
[0273] Mn: 0.3wt%;
[0274] S: 0.01wt%;
[0275] P: 0.02wt%;
[0276] Mg: 0.03wt%;
[0277] Cu: 0.05wt%;
[0278] The rest is Fe;
[0279] S604. Cool down for 40 minutes after pouring and unpack;
[0280] S605. Transfer to the shot blasting and grinding station, after air cooling, carry out shot blasting and sand removal at a temperature below 50℃, remove the pouring head, grind the flash and burrs, and transfer to the heat treatment station after passing the inspection;
[0281] S606. The heat treatment furnace is heated to 880℃, kept in the furnace for 150 minutes, cooled naturally to 700℃, and then transferred to the processing procedure after passing the air cooling inspection;
[0282] S607. Process to finished product size, and transfer to painting process after passing inspection.
[0283] The coating process is carried out as follows:
[0284] Place the fixed retaining ring and the adjustable retaining ring facing outward into acetone for ultrasonic cleaning for 0.5 h, and then blow dry;
[0285] Laser-assisted spraying for spraying of base layer and abutting layer:
[0286] For the base layer, the laser spot and the sprayed powder spot were kept in the same center, the N2 pressure was 0.8MPa, the preheating temperature was 520℃, the spraying distance was 18mm, the scanning speed was 40mm / s, the powder feeding rate was 10g / min, and the laser irradiation power was 500W;
[0287] For the abutting layer, after the base layer is coated, the abutting layer is coated immediately, and the laser spot and the sprayed powder spot are kept coincident in the center of the circle. The N2 pressure is 0.8MPa, the preheating temperature is 520℃, the spraying distance is 18mm, the scanning speed is 20mm / s, the powder feeding rate is 20g / min, and the laser irradiation power is 600W;
[0288] The diameter of the laser spot is 5 mm; the diameter of the spray powder spot is 4 mm;
[0289] The base layer includes the following raw materials in parts by weight:
[0290] Al: 6 parts; Sn: 1.55 parts;
[0291] The abutting layer includes the following raw materials in parts by weight:
[0292] Al: 20 parts; Cr: 2 parts; Cu: 1 part; Nano-silica: 1 part; WC: 0.2 parts.
[0293] Place the matching vacuum air conditioning tire cover on the outside of the obtained rim (a set of 10 is required), take one of them, and place it under 9MPa and room temperature for 24 hours. If there is no leakage, set the initial air pressure to 9MPa, and measure the air pressure after 30 days. The air pressure value is 8.6MPa;
[0294] The obtained tire was assembled on a suitable wheel, and emergency braking was performed 50 times under the conditions of a driving speed of 25 km / h and an air pressure of 9 MPa to measure the offset between the rim and the tire. The evaluation results were expressed by setting Example 1 as 1, and the offset of the remaining examples divided by Example 1 was used as the representative value of the final offset. The offset of this test was 1.02.
[0295] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.
Claims
1. A composite rim, characterized in that: The invention comprises a rim body, a fixed retaining ring is arranged outside one side of the rim body, an adjustable retaining ring is arranged on the other side of the rim body relative to the fixed retaining ring, and an outer sealing coating is arranged on the outward side of the fixed retaining ring and the adjustable retaining ring; the outer sealing coating is obtained by laser spraying.
2. A composite rim according to claim 1, characterized in that: The outer sealing coating comprises a base layer arranged on the inner side and an abutting layer arranged on the base layer, the base layer has a thickness of 50-100 μm, and the abutting layer has a thickness of 200-300 μm; The base layer includes the following raw materials in parts by weight: Al: 6-8 parts; Sn: 1.5-2.5 parts; The abutting layer includes the following raw materials in parts by weight: Al: 20-30 parts; Cr: 2-4 parts; Cu: 1-2 parts; Nano-silica: 1-2 parts; WC: 0.2-0.4 parts.
3. A composite rim according to claim 1, characterized in that: The outer sealing coating is operated according to the following steps: Place the fixed retaining ring and the adjustable retaining ring facing outward into acetone for ultrasonic cleaning for 0.5-1h, and then blow dry; Laser-assisted spraying for spraying of base layer and abutting layer: For the base layer, keep the laser spot and the spray powder spot coincident in the center, the N2 pressure is 0.8-1MPa, the preheating temperature is 520-550℃, the spraying distance is 18-20mm, the scanning speed is 40-50mm / s, the powder feeding rate is 10-15g / min, and the laser irradiation power is 500-600W; For the abutting layer, after the base layer is coated, the abutting layer is coated immediately, and the laser spot and the sprayed powder spot are kept coincident in the center of the circle, the N2 pressure is 0.8-1MPa, the preheating temperature is 520-550℃, the spraying distance is 18-20mm, the scanning speed is 20-25mm / s, the powder feeding rate is 20-25g / min, and the laser irradiation power is 600-800W; The diameter of the laser spot is 5-6 mm; the diameter of the spray powder spot is 4-5 mm.
4. A composite rim according to claim 1, characterized in that: A clamping groove is arranged on the rim body at the lower part of the adjustable retaining ring, a locking ring is clamped in the clamping groove, and the locking ring is arranged to abut against a side of the adjustable retaining ring away from the fixed retaining ring; The locking ring comprises a clamping block inserted into the clamping groove, an obliquely arranged oblique block is arranged on the clamping block, an oblique positioning surface is arranged at a position of the oblique block relative to the adjustable retaining ring; an oblique abutting surface abutting against the oblique positioning surface is arranged at a position of the adjustable retaining ring corresponding to the oblique block; The adjustable retaining ring includes an abutting plate abutting against the rim body, a vertical baffle is arranged on the side of the abutting plate away from the fixed retaining ring, a transverse plate is arranged on the side of the vertical baffle away from the fixed retaining ring, and the connection between the abutting plate and the vertical baffle is obliquely arranged on the side adjacent to the rim body to form an oblique positioning surface.
5. A composite rim as claimed in claim 3, characterized in that: An auxiliary groove is also arranged on one side of the clamping groove close to the rim body; A transition groove is arranged at the position of the auxiliary groove corresponding to the abutment plate, and one end of the transition groove facing the fixed retaining ring is arranged at the upper part of the auxiliary groove; one end of the transition groove away from the fixed retaining ring is smoothly connected to the oblique positioning surface.
6. A composite rim according to claim 4, characterized in that: The side of the abutment plate facing the rim body is provided with an annular groove, and an annular sealing ring is provided in the annular groove.
7. A composite rim according to claim 4, characterized in that: The side of the clamping groove facing away from the fixed retaining ring is a first clamping angle, and the side close to the fixed retaining ring is a second clamping angle; the second clamping angle is greater than the first clamping angle; the first clamping angle is a right angle; a positioning clamping groove is formed between the clamping block and the oblique block to cooperate with the first clamping angle.
8. The composite rim according to claim 1, characterized in that: An outer protective plate is arranged on the rim body on one side of the adjustable retaining ring, a plurality of bolt connection holes are arranged on the outer protective plate, an oblique connecting plate is arranged between the outer protective plate and the rim body, a plurality of ventilation holes are arranged on the oblique connecting plate; the adjustable retaining ring is arranged in an integrated manner; a valve channel is arranged on the hub body, and a valve concave sealing ring is arranged on the outward side of the valve channel.
9. A method for preparing a composite rim according to any one of claims 1 to 8, characterized in that: The steps include: S1. Develop an iron-mold-coated sand composite rim mold according to the size of the composite rim; S2. Conduct full-size inspection on the iron-mold-covered sand composite rim mold, and transfer it to the foundry workshop for production after it passes the inspection; S3. Before production, the iron mold coated with sand composite rim mold is heated to 230 ° C by electric heating pipe, and the coated sand is shot into the composite rim cavity by a sand shooting machine. After 3 minutes, the mold is opened, the vent core is lowered, and the surrounding sealing paste is applied to close the upper and lower boxes and tighten them, and then the casting material is poured into the casting section; S4. Cool down for 40 minutes after pouring and unpack; S5. Transfer to the shot blasting and grinding station, after air cooling, carry out shot blasting and sand removal at a temperature below 50℃, remove the pouring head, grind the flash and burrs, and transfer to the heat treatment station after passing the inspection; S6. The heat treatment furnace is heated to 880℃-900℃, kept in the furnace for 150 minutes, cooled naturally to 700℃, and then transferred to the processing procedure after passing the air cooling inspection; S7. Process to finished product size, and transfer to painting process after passing inspection.
10. The method for preparing a composite rim according to claim 9, characterized in that: The raw materials of the iron mold covered with sand composite rim mold include the following raw materials in parts by mass: Silica sand: 100-120 parts; Bentonite: 3-5 parts; Water glass: 1-2 parts; Titanium dioxide: 0.5-1 part; The pouring is carried out as follows: The casting material is added into a medium frequency electric furnace, heated to 1500-1520°C and then subjected to a spheroidizing treatment. The casting material includes the following raw materials: 3.7wt%≤C≤3.9wt%; 2.1wt%≤Si≤2.6wt%; 0.3wt%≤Mn≤0.5wt%; 0.01wt%≤S≤0.03wt%; 0.02wt%≤P≤0.05wt%; 0.03wt%≤Mg≤0.06wt%; 0.05wt%≤Cu≤0.07wt%; The rest is Fe; The coating process is carried out as follows: Place the fixed retaining ring and the adjustable retaining ring facing outward into acetone for ultrasonic cleaning for 0.5-1h, and then blow dry; Laser-assisted spraying for spraying of base layer and abutting layer: For the base layer, keep the laser spot and the spray powder spot coincident in the center, the N2 pressure is 0.8-1MPa, the preheating temperature is 520-550℃, the spraying distance is 18-20mm, the scanning speed is 40-50mm / s, the powder feeding rate is 10-15g / min, and the laser irradiation power is 500-600W; For the abutting layer, after the base layer is coated, the abutting layer is coated immediately, and the laser spot and the sprayed powder spot are kept coincident in the center of the circle, the N2 pressure is 0.8-1MPa, the preheating temperature is 520-550℃, the spraying distance is 18-20mm, the scanning speed is 20-25mm / s, the powder feeding rate is 20-25g / min, and the laser irradiation power is 600-800W; The diameter of the laser spot is 5-6 mm; the diameter of the spray powder spot is 4-5 mm; The base layer includes the following raw materials in parts by weight: Al: 6-8 parts; Sn: 1.5-2.5 parts; The abutting layer includes the following raw materials in parts by weight: Al: 20-30 parts; Cr: 2-4 parts; Cu: 1-2 parts; Nano-silica: 1-2 parts; WC: 0.2-0.4 parts.